Religion and technology in the 21st century faith in the e-world - George, Susan, 1967- (Hershey, PA : Information Science Pub., 2006)
"This book examines the unique synergy between religion and technology, and explores the many ways that technology is shaping religious expression, as well as ways that religion is coming to influence technology"--Provided by publisher.
Technology and religion -- Defining technology -- Why technology and not science? -- Defining religion -- Why technology and religion? -- The philosophy of technology -- What is the problem: technological determinism -- Approaches to the technological problem -- Technology and identity -- 21st century technologies -- Information and communication technologies -- Artificial intelligence -- Ubiqutious computing and ambient intelligence -- Virtual AI -- Future directions and the challenges -- The penetration of AI technologies in society -- The relational machine -- Mind where you're going -- The techno-religious age -- The search beyond Google -- Mutual transcendence -- World religions -- Technology for religion -- 21st century Christianity -- Christendom: the ultimate defiance? -- Failures of Christianity -- What is church? -- Church and the Internet -- Examples of Internet and church -- Function of the Internet and church -- Typologies for Internet entities and church -- Christian community: real and virtual -- Real and virtual Christian communities -- Interactive life -- The question of presence -- The theology of technology -- Theology and cybertheology -- Moral machines or people? -- Artificial identity: the image of God -- The philosophy of AI -- What is computation? -- Computationalism: can a machine think? -- People, machines, and the non-algorithmic -- Principle-based engineering -- Constraint-based computation -- Situated computation -- Constraint systems and evolutionary systems -- Beyond culture -- A transcultural world -- Without a technology and religion synergy.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Computers -- Religious aspects -- Christianity; Internet -- Religious aspects -- Christianity; Computers -- Religious aspects; Internet -- Religious aspects; RELIGION -- Christianity -- General; BODY, MIND & SPIRIT -- Gaia & Earth Energies; Electronic books